Liveable street design guideline for youth community place in Sudimoro Café Corridor, Malang City / Julia Oktaviani Hardiyanto and Prananda Navitas - Hardiyanto, Julia Oktaviani; Navitas, Prananda (2022)
A drastic land use transformation in Malang City happens at Ikan Tombro Street, which has developed into the Sudimoro Cafe Corridor because of its prospective location. However, this youth-bustling built-up area cannot provide appropriate facilities for its visitors. Consequently, several problems appear gradually each year, such as floods. Furthermore, the lack of parking areas causes heavy traffic, making this area unsafe for pedestrians. Together with government policy for developing the corridor, a liveable street approach can be a strategy to provide decent infrastructure and solve different problems at once in this area. The proposed paper describes research to create design guidelines for Sudimoro Cafe Corridor with the liveable street concept to promote the youth community place in Malang City. First, an online questionnaire among Malang City residents was distributed to evaluate the importance and performance of liveable street attributes. The researchers also interviewed relevant stakeholders to assess liveable street components further. Finally, a descriptive qualitative analysis with triangulation approach was conducted by combining the result from the previous analysis, relevant liveable street literature, and local regulations to produce the desired output. The findings of this study resulted in a liveable street design guideline highlighting safety, convenience, circulation and parking, open space, pedestrians, activities, and uniqueness that will interest local decision-makers involved in the planning industry. Besides that, this research also contributes to a deeper understanding of the factors influencing liveability in urbanized areas from the youth perspective. This understanding will be of particular interest to decision-makers as it will help them create urban spaces that are more welcoming and inclusive.